LINGUISTIC FEATURES OF FRENCH POLICE TERMINOLOGY - Nguyen, Thi Hue (VNU Journal of Foreign Studies, 2025)
In light of the growing need for enhanced international legal cooperation, mastering the system of French police terminology has become essential in administrative, judicial, and specialized translation activities. This study focuses on identifying the prominent linguistic features of this terminology class, grounded in modern terminological theories. The data was collected from legal texts, administrative documents, and specialized databases, and analyzed using qualitative methods combined with descriptive linguistic models. The findings reveal that French police terminology is characterized by monosemy, specificity, structural stability, a high degree of conceptual systematization, and strong influence from legal and cultural factors. The study affirms both the linguistic significance and practical application of this terminology within Francophone legal contexts. The results can be applied in teaching French for specific purposes, developing professional materials, and supporting bilingual translation in the fields of police and judiciary.